Carbon source utilization profiles suggest additional metabolic interactions in a synergistic linuron‐degrading bacterial consortium. Issue 1 (12th November 2012) - Horemans, Benjamin; Smolders, Erik; Springael, Dirk
Abstract A bacterial triple‐species consortium that synergistically metabolizes the phenylurea herbicide linuron was studied to determine whether synergy is extended toward the metabolism of other C‐sources. The metabolic performance and range of the individual consortium members were compared with those of paired and three‐species combinations in Biolog GN2 MicroPlate assays. The strain combinations showed an increase in the rate and extent of utilization of 80% of the C‐sources that were utilized by either one or more of the individual consortium members and the additional utilization of eight C‐sources for which oxidation was not observed for the individual strains. When one of the three strains was replaced by bacterial strains 'foreign' to the consortium, either belonging to the same genus or to other genera, mainly antagonistic effects occurred. The data suggest that the consortium members cooperate in the metabolism of C‐sources in addition to linuron. This feature can contribute in consolidating consortium composition when linuron is absent or present at low concentrations.